Identity construction and impression management across digital sport platforms: a PRISMA 2020 systematic review of studies published between 2015 and 2026 - Anisa Sholiha Mia; Bram Sujadesman; Jeki Haryanto (JRTI (Jurnal Riset Tindakan Indonesia), 2026)
With the rise of social media, there is a change in the way athletes create, manage and convey their images. They no longer depend on traditional media outlets to shape their reputation but can now use digital platforms to craft their image directly. While there have been lots of studies in this field that span sport sociology, sport communication, and digital media, most results are disjointed, and there is barely any research on how self-presentation, impression management, athletic identity and personal branding come together in the connected context. This review attempts to fill some gaps in the literature by consolidating the empirical works done on athletes' self-presentation in digital environments. According to the PRISMA 2020 guidelines, a Scopus search was carried out that turned up 649 documents. The Scopus search was conducted in January 2026 using the search terms "social media", "Instagram", "TikTok", "self-presentation", "impression management", "personal branding", and "athletes", combined through Boolean operators. Two independent reviewers screened all records following the PRISMA 2020 protocol, with disagreements resolved through discussion. Inter-rater reliability reached Cohen's κ = 0.87. Study quality was assessed using the FICO appraisal framework, while thematic synthesis followed the procedures proposed by Thomas and Harden (2008). Once duplicates were eliminated (n =6), 643 records were checked; out of these, 582 were either in the wrong type, language or were completely off the topic of the study. Finally, after assessing 61 full-text articles and discarding 51 for not meeting the requirements of self-presentation through an empirical lens or not available, only 10 papers emerged for thematic synthesis. The analysis covered topics such as image building, identity construction, self-promotion techniques, and environmental factors affecting online self-presentation. The three main outcomes were: 1) Athletes playfully weave together aspects of their public and private faces, 2) True or authentic image is primarily an athlete's branding tool, though commercially driven, and 3) Gender, characteristics of a social media platform and the influence of advertising are factors that define how athletes use the medium. In conclusion, the review has laid out the theory, practical guidance, and the scope of further research on this subject to different stakeholders such as sportspersons, trainers, and advertisers.